Gugatan Sederhana Dalam Proses Beracara - Herul; Kairuddin Karim; Abdillah AR; Khaerul Mannan (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
This study aims to find out the rules that were changed in the Supreme Court Regulation Number 2 of 2015 after the issuance of the Supreme Court Regulation Number 4 of 2019 concerning Procedures for Settlement of Simple Lawsuits and to find out the process of proceedings for simple lawsuits based on Supreme Court Regulation Number 4 of 2019 concerning Simple Lawsuit Settlement Procedures. This research uses normative legal research, using a research approach, namely the statute approach or juridical approach. Research results in The legal substance that was amended in Perma Number 2 of 2015 After the issuance of Perma Number 4 of 2019 concerning Procedures for Settlement of Simple Lawsuits, such as the amount of the value of the material lawsuit, the domicile of the defendant, regarding the use of electronic administration, regarding the presence of the parties in the trial, regarding the placement confiscation of guarantees, concerning claims which were acknowledged and refuted by the defendants, concerning decisions which were not objected to and concerning the determination of security (execution).